Comparison on Structural Design Using Three (3) Structural Softwares - Noorfakhriah binti Yaakub, Noorfakhriah (Universiti Teknologi Petronas, 2009)
A rapid development within the field of civil engineering structural design methods and techniques and software designs that has taken place over the last years offers new possibilities for designers of structural design through the use of Building Information Modeling (BIM) concept. The concept of generating computable data set of building and modeling in the construction industry is very definite. With a lot of softwares available in the market for structural consulting firms to choose, there is a need to find the software that produce optimum results. For this approach, a same structural design is done using three different softwares, namely Esteem, Orion, and STAAD Pro Structural Software, with fixed parameters to see the difference in the design output. In this case, a water tank structure architectural design is obtained and roughly designed before being transferred into the softwares. The designs include beam, column, slabs, and foundation where certain parameters such as element size and density are fixed in order to find the most powerful output. This Final Year Project thesis is a theoretical work extracted from study material, ranges of codes of practice documents, and web-source referenced. The work was aimed towards giving a state-of-the-art introduction to software technology of structural design as well as comparing the use of the softwares in industry